Marginal sights : staging the Chinese in America - Moy, James S., 1948- (Studies in theatre history and culture., 1993)
Since the beginning of the Western tradition in drama, dominant cultures have theatrically represented marginal or foreign racial groups as "other" & different form "normal" people, not completely human, uncivilized, quaint, exotic, comic. Playwrights and audiences alike have been fascinated with racial difference, and this fascination has depended upon a process of fetishization. By the time Asians appeared in the United States, the framework for their constructed Lotus Blossom and Charlie Chan stereotypes had preceded them.